Pengenalan Dasar Algoritma Pemograman Bagi Mahasiswa - Dewi, Nurika Kartika; ., Yahfizham (Journal Of Informatics And Busisnes, 2023)
Most lay people who hear the word algorithm wonder whether it refers to programming languages, computer science, mathematics. This is not wrong because algorithms are closely related to computing. Usually the algorithm itself shows the stages of solving a problem. The word algorithm comes from the family name of the Persian mathematician Muhammad ibn Musa ak-Khwarizmi. Algorithms are a general way to solve certain cases. Algorithms are intended to help in applying a system to a particular problem. When writing algorithms, they can use natural language or mathematical notation so they cannot be run on a computer. In everyday life, we have created algorithms to solve problems or challenges. Algorithms play a very important role in computer programming because algorithms are the heart of computer science.